2018
DOI: 10.1128/mbio.01219-17
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow between Divergent Cereal- and Grass-Specific Lineages of the Rice Blast Fungus Magnaporthe oryzae

Abstract: Delineating species and epidemic lineages in fungal plant pathogens is critical to our understanding of disease emergence and the structure of fungal biodiversity and also informs international regulatory decisions. Pyricularia oryzae (syn. Magnaporthe oryzae) is a multihost pathogen that infects multiple grasses and cereals, is responsible for the most damaging rice disease (rice blast), and is of growing concern due to the recent introduction of wheat blast to Bangladesh from South America. However, the gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
206
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(242 citation statements)
references
References 66 publications
18
206
0
3
Order By: Relevance
“…Studies focused on recently divergent species have identified large introgressed tracts (>1 Mb), consistent with recent admixture (Gladieux et al. ; Maxwell et al. ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Studies focused on recently divergent species have identified large introgressed tracts (>1 Mb), consistent with recent admixture (Gladieux et al. ; Maxwell et al. ).…”
Section: Discussionmentioning
confidence: 65%
“…; Gladieux et al. ). Therefore, to some extent, these results are expected as recently diverged species are not likely to have accumulated many hybrid incompatibilities (Matute et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…e . poly‐specialists, such as the rice blast fungus Pyricularia oryzae ; Gladieux et al ., ; Valent et al ., ). Depending on time‐based, geographic and genetic factors (Nosil et al ., ), speciation can then unfold relatively rapidly between pathogen populations (Giraud et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is capable of mass destruction to valuable plant crops such as rice and wheat, as well as barley, finger millet, and foxtail millet (Gladieux et al 2018). In fact, each year M. oryzae causes an estimated $66 billion in economic damage to rice crops, destroying enough food to have fed 60 million people (Pennisi 2010).…”
Section: Introductionmentioning
confidence: 99%